Prenatal Therapy with Magnesium Sulfate and Its Correlation with Neonatal Serum Magnesium Concentration - García Alonso, L.; Pumarada Prieto, M.; González Colmenero, E.; Concheiro Guisán, A.; Suárez Albo, M.; Durán Fernández-Feijoo, C.; González Durán, L.; Fernández Lorenzo, J. R. (American Journal of Perinatology, 2018)
Introduction Antenatal magnesium sulfate (MgSO4) administration has shown to be effective in minimizing cerebral palsy and severe motor dysfunction at the age of 2 years. The aim of this study is to determine the relationship between the magnesium dose delivered to the mother and the magnesium concentration in the neonates.Materials and Methods A prospective cohort study was conducted on neonates of less than 32 weeks' gestation admitted to the neonatal intensive care unit of University Hospital Complex of Vigo from December 2012 to July 2015. Comparative analysis of magnesium levels between the groups of neonates exposed to MgSO4 and the control group.Results A total of 118 neonates were included in the study. The mothers of 62 of them had received MgSO4 as a neuroprotective agent. There was a significant correlation between the full dose of MgSO4 received by the mother and the levels of magnesium in the neonate in the first 24 hours of life (r2 = 0.397; p < 0.001).Conclusion The MgSO4 dose received by the mother has a linear relationship with the magnesium levels obtained in neonates.
Keywords: magnesium sulfate; neuroprotection; serum magnesium concentration; maternal dose